Oxidative stress, free radicals and antioxidants: potential crosstalk in the pathophysiology of human diseases - Chaudhary, Priya; Janmeda, Pracheta; Docea, Anca Oana; Yeskaliyeva, Balakyz; Abdull Razis, Ahmad Faizal; Modu, Babagana; Calina, Daniela; Sharifi-Rad, Javad (Frontier, 2023)
Introduction: Free radicals are reactive oxygen species that constantly circulate through the body and occur as a side effect of many reactions that take place in the human body. Under normal conditions, they are removed from the body by antioxidant processes. If these natural mechanisms are disrupted, radicals accumulate in excess and contribute to the development of many diseases. Methodology: Relevant recent information on oxidative stress, free radicals, reactive oxidative species, and natural and synthetic antioxidants was collected by researching electronic databases such as PubMed / Medline, Web of Science, and Science Direct. Results: According to the analysed studies, this comprehensive review provided a recent update on oxidative stress, free radicals and antioxidants and their impact on the pathophysiology of human diseases. Discussion: To counteract the condition of oxidative stress, synthetic antioxidants must be provided from external sources to supplement the antioxidant defense mechanism internally. Because of their therapeutic potential and natural origin, medicinal plants have been reported as the main source of natural antioxidants phytocompounds. Some non-enzymatic phytocompounds such as flavonoids, polyphenols, and glutathione, along with some vitamins have been reported to possess strong antioxidant activities in vivo and in vitro studies. Thus, the present review describes, in brief, the overview of oxidative stress-directed cellular damage and the unction of dietary antioxidants in the management of different diseases. The therapeutic limitations in correlating the antioxidant activity of foods to human health were also discussed.